2003
DOI: 10.2139/ssrn.434605
|View full text |Cite
|
Sign up to set email alerts
|

Income Distribution and Social Expenditures: A Cross-National Perspective

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 44 publications
1
27
1
6
Order By: Relevance
“…We briefly review the growing literature on redistribution by governments (and/or social policy) and income inequality. The relationship between economic inequality and social spending is one of mutual interdependency in which it is crucial to distinguish specific types of social spending, which are affected by different aspects of inequality (Swabisch et al, 2003). Smeeding (2002) showed that social policies, wage distributions, time worked, social and labor market institutions and demographic differences all have some influence on why there are large differences in inequality among rich nations at any point in time.…”
Section: Social Protection and Income Inequality Across Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…We briefly review the growing literature on redistribution by governments (and/or social policy) and income inequality. The relationship between economic inequality and social spending is one of mutual interdependency in which it is crucial to distinguish specific types of social spending, which are affected by different aspects of inequality (Swabisch et al, 2003). Smeeding (2002) showed that social policies, wage distributions, time worked, social and labor market institutions and demographic differences all have some influence on why there are large differences in inequality among rich nations at any point in time.…”
Section: Social Protection and Income Inequality Across Countriesmentioning
confidence: 99%
“…Source: Ferranini and Nelson (2002) However, the results in Table 1 do not show the redistributive impact of separate parts of social protection systems. Recent literature suggests that the determination of the relationship between social expenditures and inequality should be carried out on a disaggregated basis (see Swabisch et al, 2003). Ferrarini and Nelson (2002) showed that only a limited number of studies have attempted to specify the link between specific social transfer programs and income inequality.…”
Section: Redistribution By Government = (Primary Income -Disposable Imentioning
confidence: 99%
“…They show that higher inequality tends to cause higher levels of redistribution, because the median voter favors the more redistribution, the further away she is from the mean income. Hayes et al (1991) and Schwabish et al (2006), among others, confirm empirically that the income distribution indeed impacts social expenditures. The results in the literature thus suggest that there is an effect of redistributive policies on levels of inequality, but, at the same time, inequality also influences governments' policies.…”
mentioning
confidence: 59%
“…Especially Anglo-Saxon countries do not seem to be prepared to sustain the high protection levels prevailing in other countries with the same level of income. Swabish et al (2006) assembled data to examine the cross-national effects of income inequality and trust on social expenditures. Their results suggest that as the 'rich' become more distant from the middle processes and to provide a coordinating framework for member states to exchange policy ideas and practices.…”
Section: Tests On the Linkages Between Social Protection And Povertymentioning
confidence: 99%